Aqueous, One-Pot, Three-Component Reaction for Efficient Synthesis of 2-[4-(Arylsulfonyl)piperazin-1-yl]-1,3-benzothiazole, ‑1H-benzimidazole, or -1,3-benzoxazole Derivatives - Dileep, Kommula; Murty, M. S. R. (Synlett, 2017)
A simple and efficient synthetic protocol has been developed involving a one-pot three-component reaction of a 2-chlorobenzazole, piperazine, and an arenesulfonyl chloride under aqueous conditions at room temperature in the absence of a catalyst, ligand, or base. By using this protocol, a variety of 2-[4-(arylsulfonyl)piperazin-1-yl]-1,3-benzothiazole, -1H-benzimidazole, and -1,3-benzoxazole derivatives were synthesized in excellent yields.
Keywords: chlorobenzazoles; piperazine; arenesulfonyl chlorides; benzothiazoles; benzoxazoles; benzimidazoles